Beta-alanine supplementation improves aerobic and anaerobic indices of performance - Wilson, J. M.; Wilson, G. J.; Zourdos, M. C.; Smith, A. E.; Stout, J. R. (Strength and Conditioning Journal, 2010)
BETA-ALANINE SUPPLEMENTATION HAS BEEN FOUND TO INCREASE INTRAMUSCULAR CARNOSINE, STRENGTH, POWER, VOLUME PER TRAINING SESSION AND A HOST OF OTHER INDICES OF AEROBIC AND ANAEROBIC CAPACITY. HOWEVER, THERE IS A NEED TO SYNTHESIZE THIS RESEARCH SO THAT THE ATHLETE AND STRENGTH COACH ALIKE CAN OPTIMALLY BENEFIT FROM BETA-ALANINE SUPPLEMENTATION. THE PURPOSE OF THIS REVIEW IS TO PROVIDE AN ANALYSIS OF STUDIES CONDUCTED ON BETA-ALANINE. THE REVIEW WILL COVER THE OPTIMAL DOSAGE OF BETA-ALANINE; ITS USE IN RESISTANCE TRAINING, INTERMITTENT, AND ENDURANCE-BASED EXERCISES; AND WHEN COMBINED WITH CREATINE IN TRAINED AND UNTRAINED INDIVIDUALS.